Pengaruh Kualitas Catatan terhadap Keakuratan Kode Penyebab Kematian di Rumah Sakit Pertamina Jaya - Regy Permata Sari; Husni Abdul Muchlis; Hosizah Hosizah; Yati Maryati (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
The accuracy of cause-of-death coding is essential for health statistics and policy-making. Incomplete, inaccurate, and unclear documentation by physicians can lead to coding errors and reduce the validity of mortality data. This study aimed to analyze the effect of documentation quality on the accuracy of cause-of-death coding at Pertamina Jaya Hospital. This quantitative study used a cross-sectional design and was conducted in January 2026. The sample consisted of 56 Medical Certificates of Cause of Death (MCCD) from September–November 2024, selected using quota  sampling. Data were collected through observation and analyzed using univariate and bivariate analyses with logistic regression. The results showed that 14 MCCDs (25%) had accurate cause-of-death coding, while 42 MCCDs (75%) were inaccurate. Poor-quality documentation was found in 30 MCCDs (54%), while good-quality documentation was found in 26 MCCDs (46%). Bivariate analysis demonstrated a significant effect of documentation quality on coding accuracy (p = 0.037). An odds ratio of 4.062 indicated that good-quality documentation had four times greater odds of producing accurate cause-of-death codes, explaining 12.1% of the variance in coding accuracy (R² = 0.121). The study concludes that standard operating procedures and training for physicians and coders are needed to improve accuracy and validity of mortality data.